Transaction cost pricing inside BRICS IPOS - Yanagui, Nancy Rie (2020)
This research aims to provide theoretical and empirical details about IPOs’ banking transaction costs for the BRICS market and its possible pricing influence. For this study fees pricing from 2015 until 2019, of about 1149 Initial Public offerings from Brazil, Russia, India, and China were analyzed, based on the Transaction cost theory. Through a multiple regression analysis, empirical test results suggested that pricing charged by the financial institutions is impacted by IPO size, timing for issuing the IPO days and no evidence was found relative to market concentration. Also, there is evidence that international issuances have lower costs and high technology companies have higher transaction costs. One of the limitations of this study is the period: five years. From this result organizations can understand transactions costs behavior better and potentially reduce their transactions with financial institutions. The benefit that this study brings is a potential advantage to the secondary market, where lower prices can benefit investors from the stock market and more companies can be listed. Most of the previous literature had performed an investigation in transaction costs for developed countries, however little is known about banking transaction costs for developing economies, specifically in the Primary Equity Capital Markets arena from BRICS.